2005
DOI: 10.1177/1043454205281763
|View full text |Cite
|
Sign up to set email alerts
|

An Innovative Approach to the Care of Patients on Phase I and Phase II Clinical Trials: The Role of the Experimental Therapeutics Nurse

Abstract: The tremendous strides in survival rates for childhood malignancies in large part can be attributed to the clinical trial mechanism. New and innovative therapies are being developed in the laboratory in an attempt to find a cure for those children who have relapsed or have refractory disease. Phase I and phase II clinical trials move this science from the laboratory to the patient's bedside. With increasing frequency, the oncology staff nurse may be managing the care of a patient receiving a phase I or phase I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0
3

Year Published

2006
2006
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 23 publications
0
22
0
3
Order By: Relevance
“…We conclude that home pages are being used by young patients with cancer in a way that may provide informational and psychosocial support, but this use seems to be confined at present to a small proportion of this population. Nevertheless, home pages clearly are an additional Internet resource for young cancer patients that can be added to the psychosocial and informational Internet supports already flagged in other research reports (Carlson, Reilly, & Hitchens, 2005;Decker, Phillips, & Haase, 2004;Kelly & Porock, 2005;Suzuki & Kato, 2003). The home pages are potentially a useful resource not just for the young patients who might create or access them but also for oncology professionals such as psychologists and nurses, both as source of information about patients' illness perceptions and an alternative resource to which patients and families can be directed.…”
Section: Discussionmentioning
confidence: 99%
“…We conclude that home pages are being used by young patients with cancer in a way that may provide informational and psychosocial support, but this use seems to be confined at present to a small proportion of this population. Nevertheless, home pages clearly are an additional Internet resource for young cancer patients that can be added to the psychosocial and informational Internet supports already flagged in other research reports (Carlson, Reilly, & Hitchens, 2005;Decker, Phillips, & Haase, 2004;Kelly & Porock, 2005;Suzuki & Kato, 2003). The home pages are potentially a useful resource not just for the young patients who might create or access them but also for oncology professionals such as psychologists and nurses, both as source of information about patients' illness perceptions and an alternative resource to which patients and families can be directed.…”
Section: Discussionmentioning
confidence: 99%
“…Hinds et al (1997) concluded that the decision to enroll a child in Phase I studies or discontinue treatment altogether was extremely difficult for the majority of parents. Other research studies found parents expressing concern that their child might be used as a "guinea pig" in experimental therapies yet continuing to exhibit a sense of humanity by their desire to help the cause of cancer research (Carlson et al, 2005).…”
Section: Respect For Persons: Definition and Applicationmentioning
confidence: 99%
“…Horstmann et al (2005), who analyzed 460 trials sponsored by the Cancer Therapy Evaluation Program at the National Cancer Institute between 1991 and 2002, found an overall response rate of 10.6% and an overall toxic death rate of 0.49%. Also, Carlson, Reilly, and Hitchens (2005) described the creation of an innovative nursing role, called the experimental therapeutics nurse, that merges various traditional roles of a bedside nurse, research assistant, and nurse educator to provide expert and continuous care to patients and families enrolled in phase I or phase II studies. Lack of expertise in phase I studies and fragmented care often associated with phase I clinical trials can present challenges to patients and families as well as nursing staff.…”
Section: Review Of Literaturementioning
confidence: 99%
“…Last, although it may be ethically and logistically challenging, research on perceptions of pediatric patients themselves may be enlightening and a worthwhile endeavor. Further exploration of innovative nursing roles and care delivery models, such as the experimental therapy nurse role suggested by Carlson, Reilly and Hitchens (2005), would also be worthwhile.…”
Section: Recommendations For Future Researchmentioning
confidence: 99%